Ovariectomy in mouflons under field conditions: a comparative assessment of midventral and flank laparotomy approaches - Frattina, Lorenza; Carbonari, Alice; Burgio, Matteo; Giannini, Francesca; Locantore, Francesco; Rizzo, Annalisa; Cicirelli, Vincenzo (Frontiers in Veterinary Science, 2024)
Ovariectomy appears to be the best method to control the density of wild ungulate populations. The aim of the present study was to compare two surgical approaches, via the flank and midline, in mouflon's ovariectomy in field conditions. Twenty female mouflons were enrolled in the study. The animals were divided randomly in two equal groups, Group F animals were gonadectomized via flank approach, while Group L animals were sterilized via linea alba access. The parameters evaluated were duration of surgery, duration of anaesthesia, recovery time, intra-and post-operative complications, intra-operative nociception and pain in the post-operative period. There were no intra-and postoperative complications. The evaluated parameters showed a very similar trend in both groups. Both techniques are found to be effective and safe in execution.